Anthelmintic effect of condensed tannins in gastrointestinal nematodes of sheep (Ovis aries) - Yoshihara, Eidi (2013)
Gastrointestinal helminthiasis infections are considerate one of the main limiting factors in sheep production worldwide. The development of parasite resistance to anthelmintics has caused significant losses of small ruminant production. In the search for new alternatives for effective control of gastrointestinal nematodes in small ruminants, phytotherapy is a promising field of research in an attempt to reduce the usage of chemical treatments, aimed at ecological production. Many plants play a crucial role in maintaining animal and human life. During human evolution many interactions with other organisms were established and they have affected each other in many ways. Plants have developed biochemical mechanisms to defend themselves from biological antagonists that act as their natural enemies. This principle has led scientists to search for bio-active compounds produced by plants against pathogens. Since these discovers their metabolites are evaluated against diseases of importance not only in public health, but also in animal production. This article presents a review of studies with tanniniferous plants scientifically tested worldwide for the control of gastrointestinal parasites in ruminants.